Comparative assessment of professional competencies of educational standards of information and measurement technologies specialty - Gordiyenko, Tetyana (Видавництво Національного університету “Львівська політехніка”, 2024)
National education standards are documents that define expected educational achievements, knowledge, skills, and competencies. These standards may vary between countries and regions, but they are important to ensure the quality of education and comparability between different education systems. An important element of each education standard is the definition of professional competencies to be acquired. The formation of such competencies should be carried out with the involvement of the main stakeholders. To evaluate professional competencies according to the standards of bachelor’s and master’s education in information and measurement technologies, their group expert evaluation was carried out by stakeholder specialists using the averaging of indicators and the Rasch model. The results of assessment by both methods and their comparison are considered. The obtained results showed their convergence. The analysis of the results obtained according to the multivariate Rasch model showed that the measurement data according to this model allows calculating established statistics both for the competencies under consideration and for the involved experts. The Rasch model can be a useful tool for assessing the importance of established professional competencies for different levels of higher education in different specialties. Experts had the most doubts about the competence of a bachelor in the ability to develop a regulatory and methodological framework for quality assurance and technical regulation and to develop a scientific and technical basis for quality management systems and certification tests, as well as the competence of a masters in the ability to manage projects and startups and evaluate their results. Therefore, these competencies require special attention during the next revision of education standards for greater balancing of the relevant competency set.
Keywords: Comparative assessment; Professional competence; Information and measurement technologies; Scale ranking; Rasch model